Madura Tourism Branding Through Literature - Harits, Imron Wakhid; Diana, Putri Nur; Fatimah, Fatimah; Chudy, Stefan; Surya, Ulvia Ika (E-Journal of Tourism; Volume 10 Number 1 (March 2023)DO - 10.24922/eot.v10i1.96016, 2023)
Literary Tourism is closely related to the contribution of literature to the development of tourism. The efforts to brand a place by maintaining the existence of culture and nature have been quite a challenge due to cultural and natural changes of globalization which is increasingly eroding the traditional culture of a place. However, Madura with its traditions, cultures, and beautiful nature make Madura different and unique from other regions. This study displays branding on Madura tourism thus the readers get to know Madura in literary works and become travel and tourism references to visit. This research focuses on how tourism branding exists in Madura poetry by D. Zawawi Imron. Therefore, this study uses a qualitative descriptive method to determine the setting of place and culture in the poetry by D. Zawawi Imron as a Madurese writer and its potential for developing Madura tourism. The results of this study figure out that the inspiration for D. Zawawi Imron's poetry was Madura as his birthplace. In his poems also found the potential for cultural and natural tourism such as Kerapan Sapi and Saronen, as well as village circumstances, Kalianget , Sumenep , and some vocabulary that reflects Madurese characteristics such as Nira and siwalan . Hopefully, Literary Tourism will make a new contribution to multidisciplinary dynamics in applied literary studies.